0066 Problems of vision, hearing and balance and risks of workplace injury. (23rd June 2014) - Palmer, Keith; D'Angelo, Stefania; Clare Harris, E; Linaker, Cathy; Coggon, David
Abstract : Objectives: To assess the role of sensory impairments and disorders of balance in occupational injury. Method: The Clinical Practice Research Datalink records all medical consultations, referrals and diagnoses in primary care for 6% of the British population. Using this register we identified 1348 working-aged patients who had consulted medical services over a 20-year period for workplace injury (cases) and 6652 matched controls. Risks were assessed in relation to visual impairment, common eye diseases, hearing loss, perforated ear drum, non-acute otitis media, and disorders of balance, using conditional logistic regression. Results: In all, 173 subjects had had an eye problem before the date of injury consultation (index date), 793 an ear problem (including 336 with impaired hearing and 482 with non-acute otitis media), and 266 a disorder of balance. No associations were found with specific eye diseases or perforation of the ear drum, but odds ratios (ORs) were moderately elevated for eye and ear problems more generally, and higher still in relation to blindness or partial sight (OR 1.90) and non-acute otitis media (OR 2.03). The OR for consulting with disorder of balance within the 12 months immediately preceding injury consultation was 1.81 (95% CI 1.03–3.17). Conclusions: Problems of vision, impairments of hearing, and disorders of balance may all carry a moderately increased risk of occupational injury.